The Effect of Intrinsic Motivation and Financial Compensation on Affective Commitment: The Mediating Role of Job Satisfaction CV. Mulya Sukanta Makmur - Nadila Amanda; Muafi Muafi (Syntax Corporation Indonesia, 2023)
This study examines and analyzes the effect of intrinsic motivation and financial compensation on affective commitment: the mediating role of job satisfaction. The research method used in this study is a quantitative research method by distributing questionnaires to respondents. The population studied in this study were employees of CV. Mulya Sukanta Makmur numbered 70 people. The data analysis method used in this study isStructural Equation Model (SEM) by using Partial Least Square (PLS). The results of this study are that there is a positive and significant effect of intrinsic motivation on affective commitment, there is a positive and significant effect of financial compensation on affective commitment, there is a positive but not significant effect of intrinsic motivation on job satisfaction, there is a positive and significant effect of financial compensation on job satisfaction, there is a positive and significant effect of job satisfaction on affective commitment, job satisfaction does not mediate the relationship between intrinsic motivation and affective commitment, job satisfaction does not mediate the relationship between financial compensation and affective commitment